PERENCANAAN KEUANGAN SEBAGAI PENENTU KESEJAHTERAAN FINANSIAL KELUARGA DI ERA DIGITAL: SEBUAH SYSTEMATIC LITERATURE REVIEW - Safaruddin Safaruddin; Rachmiani Rachmiani; Eliyanti Agus Mokodompit (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze the development of studies on financial planning and family financial well-being in the digital era through a Systematic Literature Review (SLR) approach. Literature search was conducted using Publish or Perish, which yielded 452 articles from Google Scholar. After eliminating duplicates, filtering out non-peer-reviewed documents, and selecting articles based on the period 2020–2025, language, full-text access, and topic relevance, 20 articles met the criteria and were analyzed in depth. The SLR results show that digitalization presents both opportunities and risks for family financial management. Financial technology facilitates record keeping, budgeting, and investment, but it also increases consumptive tendencies and the potential for digital debt. The literature consistently emphasizes that financial literacy and financial behavior play an important role in determining the effectiveness of financial planning in improving family financial well-being. Although financial planning has a positive impact, its effectiveness is greatly influenced by self-control and the wise use of fintech. These findings underscore the need for a more integrative research model that incorporates aspects of digital literacy, financial behavior, and fintech risks to understand the dynamics of family financial well-being more comprehensively.